Sistema compacto de estaçãode tratamento de água para a Sociedade Esportiva Sanjoanense - Damasceno Júnior, José Edel (2011)
This paper aimed at improving a water treatment plant system currently used by SABEST (Torrezan WTP). A gravity-fed WTP was updated with adaptations to solve the problems presented by the Sociedade Esportiva Sanjoanense. With such adaptations, small companies and small populations can use this modern, economic and effective technique to improve the quality of their water supply. By means of studies and reports, all the Torrezan system of a compact WTP, modified to work better, gave an excellent result for clubs and small populations to obtain a low-cost water treatment.